Implementation of Financial Technology “Digital Payment” on Consumer Behavior at SMEs Depok City in Digital Transformation Era - Suci Ayu Sudari (Sekolah Tinggi Ilmu Administrasi Karya Dharma, 2024)
The presence of the digital era has changed people's behavior in carrying out activities from manual to digital. Especially after the Covid-19 pandemic, people are required to maintain physical contact when doing activities. SMEs at Depok City in implementing digital technology still not fully effective. so the study is conducted to analyze the effect of application of Financial Technology “Digital Payment” on Consumer Behavior at SMEs Depok City in Digital Transformation Era. Study method used regression analysis. Primary data was obtained by questionnaire as the instrument of collecting data. The data was processed with SPSS 23. The population in this study is Consumer of SMEs in Depok City, then the number of samples is 100 SMEs. The study showed that Digital Payment has significance effect on consumer behavior at SMEs in Depok City. SMEs need to improve the strategy specially in having transaction with consumers. SMEs are able to use digital payment for the business activities